2015
DOI: 10.3892/mmr.2015.4555
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148b enhances proliferation and apoptosis in human renal cancer cells via directly targeting MAP3K9

Abstract: Increasing evidence revealed that miRNAs, the vital regulators of gene expression, are involved in various cellular processes, including cell growth, differentiation, apoptosis and progression. In addition, miRNAs act as oncogenes and/or tumor suppressors. The present study aimed to verify the potential roles of miR148b in human renal cancer cells. miR-148b was found to be downregulated in human renal cancel tissues and human renal cancer cell lines. Functional studies demonstrated that plasmid-mediated overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…Knocking down miR-148b expression could enhance the phosphorylation of JNK.These results support our previous hypothesis that miR-148b exert anti-cancer activity in NSCLC by targeting MAPK/JNK pathway. In accordance with our study, Fang et al found that decreased miR-148b could enhance tumor cell proliferation and inhibit apoptosis in human renal cancer cells by targeting MAP3K9, which is a upstream activator of MAPK/JNK pathway [45]. At the same time, several studies have confirmed that miR148b works through the regulation of MAPK/JNK [46, 47].…”
Section: Discussionsupporting
confidence: 90%
“…Knocking down miR-148b expression could enhance the phosphorylation of JNK.These results support our previous hypothesis that miR-148b exert anti-cancer activity in NSCLC by targeting MAPK/JNK pathway. In accordance with our study, Fang et al found that decreased miR-148b could enhance tumor cell proliferation and inhibit apoptosis in human renal cancer cells by targeting MAP3K9, which is a upstream activator of MAPK/JNK pathway [45]. At the same time, several studies have confirmed that miR148b works through the regulation of MAPK/JNK [46, 47].…”
Section: Discussionsupporting
confidence: 90%
“…Even though altered expression was found in tumors of distinct histology , miR‐148b seems to be a major regulator of breast cancer. While directly targeting key players of the integrin signaling like ITGA5, ROCK1, PI3KCA/p110α as well as NRAS, miR‐148b controls a pathway involved in tumor growth and metastasis.…”
Section: Effects Of Mir‐148/‐152 Family Members On Tumorigenesismentioning
confidence: 99%
“…Many research have furnished important evidence revealing that MAP3K9 are connected with noteworthy cell biology. MAP3K9 suppresses proliferation and apoptosis in renal cancer cells by MAPK/c‐Jun N‐terminal kinase (JNK) signaling (Nie et al, ). Interference of MAP3K9 inhibits the motivation of extracellular‐signal‐regulated kinase (ERK) and p38 MAPK pathways, which further inhibits proliferation and promotes apoptosis of NP cells (Cai et al, ).…”
Section: Introductionmentioning
confidence: 99%